(untitled) (CIPEEX, 2022)
WITH A FOCUS ON THE QUALITY OF LIFE OF THE POPULATION, THE EVANGELICAL EDUCATIONAL ASSOCIATION (AEE) &NBSP; &NBSP; ¹ ACADMICA DO CURSO DE ODONTOLOGIA DO CENTRO UNIVERSITÁRIO DE ANÁPOLIS, ANACLARADLF@GMAIL.COM ² ACADMICA DO CURSO DE ODONTOLOGIA DO CENTRO UNIVERSITÁRIO DE ANÁPOLIS, GUSTAVO-PECLAT@HOTMAIL.COM ³ ACADMICA DO CURSO DE ODONTOLOGIA DO CENTRO UNIVERSITÁRIO DE ANÁPOLIS, JHOSYMENDES10@HOTMAIL.COM 4 ACADMICO DO CURSO DE ODONTOLOGIA DO CENTRO UNIVERSITÁRIO DE ANÁPOLIS, JOAOOSMARIOM@HOTMAIL.COM 5 ACADMICA DO CURSO DE ODONTOLOGIA DO CENTRO UNIVERSITÁRIO DE ANÁPOLIS, LUIZA_SANTOS9@HOTMAIL.COM 6 PROFESSOR MESTRE, DA DISCIPLINA DE ENDODONTIA, DO CURSO DE ODONTOLOGIA DO CENTRO UNIVERSITÁRIO DE ANÁPOLIS, GIULLIANO.SERPA@UNIEVANGELICA.EDU.BR 7 PROFESSOR DA DISCIPLINA DE ORTODONTIA, DO CURSO DE ODONTOLOGIA DO CENTRO UNIVERSITÁRIO DE ANÁPOLIS 8 PROFESSOR DA DISCIPLINA DE ORTODONTIA, DO CURSO DE ODONTOLOGIA DO CENTRO UNIVERSITÁRIO DE ANÁPOLIS &NBSP; DEVELOPED THE UNIVERSITY EXTENSION PROJECT - UNIEVANGLICA ITINERANT CITIZEN, WHERE, THROUGH THE PREVENTION AND PROMOTION OF HEALTH, IT INTERVENES IN THE REALITY OF PLACES WITH GREAT DEMAND FOR SERVICES. THE UNIEVANGLICA CITIZEN ITINERANT PROJECT - WOMEN’S DAY CONSISTED IN AN ACTION TAKEN BY THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS - UNIEVANGLICA IN CELEBRATION OF THE DAY OF THE WOMAN, ON MARCH 8, 2018, HELD IN THE AMERICAN SQUARE OF BRAZIL, IN THE CITY OF ANÁPOLIS-GO. HEALTH PREVENTION AND PROMOTION ACTIVITIES WERE DEVELOPED WITH A FOCUS ON ORAL CANCER AND MALOCCLUSIONS. THE CASES OF SUSPICION OF ORAL CANCER, IDENTIFIED THROUGH PREVENTIVE ORAL EXAMS, WERE REFERRED TO THE DENTAL CLINIC OF TEACHING AT THE CENTRO UNIVERSITÁRIO DE ANÁPOLIS - UNIEVANGLICA, IN ORDER TO RECEIVE THE APPROPRIATE CONDUCTS. THE OBJECTIVE OF THE PROJECT WAS BASED ON THE AWARENESS OF THE POPULATION ABOUT SUCH DISEASES. TWENTY ACADEMICIANS FROM THE 8TH PERIOD AND THREE TEACHERS FROM THE DENTISTRY COURSE, AS WELL AS OTHER COURSES FROM THE HEALTH AREA OF €‹€‹THE CENTRO UNIVERSITÁRIO DE ANÁPOLIS - UNIEVANGLICA COLLABORATED TO HOLD THE EVENT. THE PROJECT GENERATED SOCIAL IMPACTS DUE TO THE FACT OF EVALUATING THE REALITY OF THE POPULATION AND OFFERING ESSENTIAL INFORMATION PERTINENT TO HEALTH CARE. EFFECTIVE ACTIONS THAT ADDRESS RELEVANT ISSUES, AIMED AT PREVENTION, DETECTION, AWARENESS AND GUIDANCE ON POSSIBLE TREATMENTS, ARE FUNDAMENTAL AND PRODUCE POSITIVE RESULTS. PALAVRAS-CHAVE (OU KEYWORDS, OU PALABRAS CLAVE): ORAL CANCER. DENTISTRY. HEALTH PROMOTION.